Human Capital Investment and Sustainable Development in Algeria: An Empirical Analysis from 1992 to 2021 - Lamia, Dr. Rabia (The journal of contemporary issues in business and government, 2023)
This study delves into the significance of human capital investment in fostering sustainable development in Algeria, spanning a comprehensive three- decade period from 1992 to 2021. To emphasize the role of this investment in bolstering one of the cornerstones of sustainable development, particularly the economic dimension, we have meticulously selected variables intricately tied to human capital. These chosen variables are pivotal to our endeavor to elucidate the interplay between human capital and sustainable development. Through this approach, we aim to provide a nuanced comprehension of how investments in various facets of human capital, including education, skill enhancement, and vocational training, can serve as catalysts for both economic growth and the promotion of sustainable development. Moreover, our strategic variable selection extends beyond immediate impacts, seeking to unveil the enduring effects that ripple through time, shaping the economic landscape and paving the way for a sustainable future. Our methodology employs the Vector Autoregressive (VAR) model, a robust framework for our analysis. The results we've obtained corroborate the notion that investments in human capital, in all their diverse forms, exert a positive influence on both the economic growth and the sustainable development of Algeria throughout the study period.